UJI ORGANOLEPTIK KERTAS KOMPOSIT BERBAHAN KERTAS BEKAS DAN AMPAS KELAPA (Cocos nucifera L.) - Retno Prasetia; Purbawati Purbawati; Halikianoor Halikianoor (Journal of Sustainable Transformation, 2022)
Coconut dregs is a waste that contain cellulose as a material for making composite paper. This study aimed to know the quality of this composite paper based on organoleptic test. Organoleptic tests were also carried out to determine the level of liking for paper based on the texture, color, and odor. Composite paper in this study made of coconut pulp and used HVS paper pulp combination. This designed experiment used a completely randomized design (CRD) with 3 replications of 3 treatments and a control. The data obtained were analyzed using the Anova test and the DMRT test with a level of 5%. Organoleptic test results with the addition of 15% coconut dregs (P1) showed the highest results of liking in terms of texture, fiber appearance, color, and odor. Based on DMRT test, P1 had significant different result than others. Thus, P1 was the most liking as composite paper. Furthermore, this research has the potential to be developed for physical test for justified this composite paper has a good paper quality.